2011
DOI: 10.1177/0143831x10376615
|View full text |Cite
|
Sign up to set email alerts
|

Goal setting and plant closure: When bad things turn good

Abstract: Research has shown that closedowns seem to result in increased productivity even though all productivity targets have been abandoned. The closedown case analysed in this article is different from previous research since management came to employ high goals for productivity and efficiency throughout the entire closedown process (29 months). The article argues that individuals gradually accept the demise and detach themselves from the dying organization by adopting new career goals which they can start pursuing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…Instead, closure management strategies that matter mostly pertain to justice in terms of how the closure has been communicated, and what compensation and severance packages are provided (Blau, 2006). Earlier research has studied management of informational processes in connection to closure (Stroud and Fairbrother, 2012) as well as redundancy processes (Donnelly and Scholarios, 1998) and effects of severance packages in relation to employee motivation and performance (Bergman and Wigblad, 1999; Häsänen et al, 2010), and employee grieving as well as acceptance of the organization’s ‘death’ (Butler et al, 2009). With the exception of studies by Blau (2006, 2007, 2008) however, there is a lack of systematic models relating employees’ perceptions of closure management in terms of information and compensation to employee well-being and organizational attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, closure management strategies that matter mostly pertain to justice in terms of how the closure has been communicated, and what compensation and severance packages are provided (Blau, 2006). Earlier research has studied management of informational processes in connection to closure (Stroud and Fairbrother, 2012) as well as redundancy processes (Donnelly and Scholarios, 1998) and effects of severance packages in relation to employee motivation and performance (Bergman and Wigblad, 1999; Häsänen et al, 2010), and employee grieving as well as acceptance of the organization’s ‘death’ (Butler et al, 2009). With the exception of studies by Blau (2006, 2007, 2008) however, there is a lack of systematic models relating employees’ perceptions of closure management in terms of information and compensation to employee well-being and organizational attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our data suggest that the psychological alignment of the corporation and its workforce seemed to strengthen as closure approached. Literature suggests that high levels of performance during a closure countdown period are rare, both inside and outside the automotive sector (Bergman & Wigblad, 1999; Hasanen et al, 2011). In perhaps the worst of cases, it is reported that during the GM Fremont plant closure, “workers would often sabotage the very cars they were building, leaving bolts and soft drink cans in panels for instance to rattle and annoy customers.” 16 Such sabotage led employees to achieve overtime pay while they fixed defects that they had deliberately implemented 17…”
Section: Insights and Theory Elaborationmentioning
confidence: 99%
“…However, the authors do not offer explanations regarding the causes of the effect. Finally, Hasanen et al (2011) study the role of goal setting in the closure of a medical manufacturing plant. Their findings suggest that workers' job performance during the countdown period was improved by clear goal rationale, goal efficacy and actionable plans, and tangible rewards tied to goal achievement.…”
Section: Psychological Contract Theorymentioning
confidence: 99%
“…They found reliabilities for goal specificity and goal difficulty, but due to the small sample size, were unable to report on the factor structure. Similarly, Häsänen, Hellgren, and Hansson discovered that the questionnaire had some factor reliabilities, but they failed to examine the factor structure.…”
Section: Definition and Uses Of The Conceptmentioning
confidence: 99%